Altered Fasting and Postprandial Ghrelin Response in Patients with Irritable Bowel Syndrome (IBS) - Saleem Ullah Zaffar, Talha Bin Ayub, Abdul Basit Zubair, Hajira Siddique, Aneela Shabbir, Shahzad Latif, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Alterations in ghrelin dynamics have been increasingly implicated in thepathophysiology of functional gastrointestinal disorders, yet their behavior in irritable bowel syndrome (IBS) remains insufficiently